SLC43A3 is a Biomarker of Sensitivity to the Telomeric DNA Damage Mediator 6-Thio-2’-Deoxyguanosine - Mender, Ilgen (Cancer Res, 2020)
Cell membrane transporters facilitate the passage of nucleobases and nucleosides for nucleotide synthesis and metabolism, and are important for the delivery of nucleoside analogues used in anti-cancer drug therapy. Here, we investigated if cell membrane transporters are involved in the cellular uptake of the nucleoside analogue DNA damage mediator 6-thio-2’-deoxyguanosine (6-thio-dG). A large panel of non-small cell lung cancer (NSCLC) cell lines (73 of 77) were sensitive to 6-thio-dG; only 4 NSCLC lines were resistant to 6-thio-dG. When analyzed by microarray and RNA sequencing, the resistant NSCLC cell lines clustered together, providing a molecular signature for patients that may not respond to 6-thio-dG. Significant downregulation of solute carrier family 43 A3 (SLC43A3), an equilibrative nucleobase transporter, was identified as a candidate in this molecular resistance signature. High levels of SLC43A3 mRNA predicted sensitivity to 6-thio-dG and therefore SLC43A3 could serve as a promising biomarker for 6-thio-dG sensitivity in NSCLC patients.